2004
DOI: 10.1007/978-3-540-30139-4_102
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Reasoning in Education of Deaf Students: Scientific Education and Acquisition of Portuguese as a Second Language

Abstract: Brazilian educational system is faced with the task of promoting deaf people educational rights. Presently, the deaf are integrated in the classroom along with hearing students. Qualitative Reasoning may provide tools to support Portuguese acquisition in the context of the development of scientific concepts. This study describes an experiment with eight deaf students being exposed to three articulate qualitative models organized in gradual levels of complexity. Questionnaires were used to assess ther students'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…(Bredeweg & Forbus, 2003). Published work showed that the QR approach fosters learning processes such as: establishing and completing terminology in a missing model while comparing it to a reference model (Lozano et al, 2015); providing an inductive explanation versus a mere measurement of the outcome (Petrou et al, 2014); integrating interdisciplinary knowledge (Mioduser et al, 2010); conceptual understanding of processes in ecosystems (Salle, Salles & Bredeweg, 2004); detecting errors in the process of learning a second language (Twidale et al,1990); understanding community behaviors through qualitative models (Salles & Bredeweg, 2001;.…”
Section: Three Modeling Approachesmentioning
confidence: 99%
“…(Bredeweg & Forbus, 2003). Published work showed that the QR approach fosters learning processes such as: establishing and completing terminology in a missing model while comparing it to a reference model (Lozano et al, 2015); providing an inductive explanation versus a mere measurement of the outcome (Petrou et al, 2014); integrating interdisciplinary knowledge (Mioduser et al, 2010); conceptual understanding of processes in ecosystems (Salle, Salles & Bredeweg, 2004); detecting errors in the process of learning a second language (Twidale et al,1990); understanding community behaviors through qualitative models (Salles & Bredeweg, 2001;.…”
Section: Three Modeling Approachesmentioning
confidence: 99%
“…(Bredeweg & Forbus, 2003). Published work showed that the QR approach fosters learning processes such as: establishing and completing terminology in a missing model while comparing it to a reference model (Lozano et al, 2015); providing an inductive explanation versus a mere measurement of the outcome (Petrou et al, 2014); integrating interdisciplinary knowledge (Mioduser et al, 2010); conceptual understanding of processes in ecosystems (Salle, Salles & Bredeweg, 2004); detecting errors in the process of learning a second language (Twidale et al,1990); understanding community behaviors through qualitative models (Salles & Bredeweg, 2001;.…”
Section: Three Modeling Approachesmentioning
confidence: 99%
“…(Bredeweg & Forbus, 2003). It enables establishing and completing terminology from a missing model and comparing it to a model built as a reference model (Lozano et al, 2015); providing an inductive explanation versus a mere measurement of the outcome (Petrou et al, 2014); integration of interdisciplinary knowledge (Mioduser et al, 2010); Conceptual understanding in a bilingual environment of processes in ecosystems (Salle, Salles & Bredeweg, 2004); learning a second language by detecting errors (Twidale et al,1993) and understanding of community behavior through qualitative models (Salles & Bredeweg, 2001;.…”
Section: Three Modeling Approachesmentioning
confidence: 99%